A dataset of geotechnical parameters based on international literature to characterise lithotypes in Italy - Nunzia Monte; Francesco Bucci; Federica Angela Mevoli; Michele Santangelo; Paola Reichenbach; Lucio Di Matteo; Ivan Marchesini (Scientific Data)
Abstract Geological and lithological maps provide essential spatial data for various environmental assessments and studies. However, these maps lack detailed quantitative information on the geotechnical characteristics of rocks and soils, which limits their use for modelling purposes. This study addresses this gap by compiling a comprehensive database of over 2300 geotechnical parameter records searching the international literature. Focusing on cohesion, friction angle, and porosity, we analyse their distributions across different lithotypes, emphasising their significance in slope stability modelling. For the Italian territory, the collected information was used to associate geotechnical parameters to the lithological classes as identified by Bucci et al. 2022. These types of reclassified maps may provide researchers and stakeholders with a comprehensive dataset useful for slope stability assessment and land management at small scale. Descriptive statistics and validation from grey literature underscore the dataset’s utility in enhancing geotechnical characterizations and supporting geological hazard assessments.